Sistem Informasi Geografis Pemetaan Tempat Oleh-Oleh di Kabupaten Garut Berbasis Android - Asri Mulyani; Ade Sutedi; Gina Muhtari (Institut Teknologi Garut, 2023)
Indonesia is a country that is rich in the diversity of characteristics of each region, as in the city of Garut which has regional souvenirs, one of which is dodol arrowroot, souvenirs made of leather and so on. However, currently tourists who want to buy souvenirs in Garut lack the information they get or the knowledge of tourists about the regional specialties they visit. Geographic information systems can help users find places of interest and also by mapping places where souvenirs are made to help users find information about several souvenir shops in the city of Garut. The methodology used is the Rational Unified Process which has four stages, namely Inception, Elaboration, Construction, and transition. This system is built using the React Native framework and using the JavaScript programming language. The result of this research is to create a Geographic Information System for mapping souvenir places in Garut City based on Android, it is hoped that tourists can find it easy to find souvenir locations in Garut city.